The Effect of Giving Various Doses of Cow Manure On The Growth of Rattan Stem Seedlings (Calamus Zollingeri Becc) In Polybags - Rahmawati; Gilang Ramadhan Syahputra; Yusran; Annadira; Siti Chasandra Pratiwi; Muh. Rian Pratama; Rinaldy Malik (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2024)
The fulfillment of rattan needs in the future will continue to increase, and it is estimated that rattan sources from natural forests will not be able to provide sufficient quantities. Therefore, rattan development is still needed, especially in cultivating it on community land or in community nurseries. Rattan cultivation needs to be developed by procuring good and quality rattan seedlings, one form of effort in increasing the productivity of rattan stems is through maintenance so that to obtain quality seedlings, additional materials are needed in the media to provide nutrients that support plant growth. One of the organic fertilizers that plays a role in soil quality and plant growth is cow manure compost where this fertilizer is processed animal waste or cow manure that is given to the soil to improve soil fertility. This study provides information on the effect of giving various doses of cow manure on the growth of rattan stem seedlings (Calamus zollingeri Becc) in polybags so that it can be used as a guide in utilizing the cow manure optimally. This study used a completely randomized design (CRD) consisting of five treatments, P0 = soil without cow manure (control), P1 = 1000g soil + 200g cow manure, P2 = 1000g soil + 300g cow manure, P3 = 1000g soil + 400g cow manure, P4 = 1000g soil + 500g cow manure, Each treatment was repeated 10 times so that it required as many as (5x10) = 50 experimental seed units.